2015
DOI: 10.1149/2.1101509jes
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Promoted Deposition of Ordered Pt Adlayer on Au(111) and Its Electrocatalytic Properties

Abstract: In situ scanning tunneling microscopy (STM) was used to examine the microstructures of platinum (Pt) deposited on ordered Au(111) substrate in aqueous Na 2 PtCl 6 solution saturated with carbon monoxide (CO) with and without potential control at room temperature. PtCl 6 2− complexes were reduced to Pt atoms by CO molecules and deposited on Au(111) in a hexagonal array without potential control. The adsorption of CO molecules first mobilized and rearranged Pt adatoms on Au(111) from disordered Pt aggregates to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 51 publications
(90 reference statements)
3
11
1
Order By: Relevance
“…23 Recently, we found that carbon monoxide can serve as a reductant for PtCl 6 2− , which yields a CO-capped Pt monolayer on Au(111) without potential control. 24 We substantiate the study of an ordered Pt monolayer on Au(111) by showing that the CO adlayer can be removed to expose the Pt deposit without affecting the ordered state of the Pt monolayer. This supported Pt monolayer has Pt adatoms arranged in atomic structures different from those of bulk Pt(111) electrode, which enables tailoring unique electrocatalytic properties.…”
Section: Introductionsupporting
confidence: 62%
See 4 more Smart Citations
“…23 Recently, we found that carbon monoxide can serve as a reductant for PtCl 6 2− , which yields a CO-capped Pt monolayer on Au(111) without potential control. 24 We substantiate the study of an ordered Pt monolayer on Au(111) by showing that the CO adlayer can be removed to expose the Pt deposit without affecting the ordered state of the Pt monolayer. This supported Pt monolayer has Pt adatoms arranged in atomic structures different from those of bulk Pt(111) electrode, which enables tailoring unique electrocatalytic properties.…”
Section: Introductionsupporting
confidence: 62%
“…The use of 0.1 M H 2 SO 4 saturated with hydrogen gas as the electrolyte can prevent the Pt film from oxidation during the electrode transfer process. This is different from the process reported in the previous work . The first rinsing was used to remove the extra PtCl 6 2– on the as-prepared electrode, and then the CO was removed by the following rinsing.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations